Influencia de las hormonas vegetales en el desarrollo y crecimiento del cultivo de Zucchini (Cucurbita pepo), en la zona de Babahoyo - Fernández Barragán, Gloria Stefania (2020)
The research was carried out on the premises of the "San Pablo" Farm of the Technical University of Babahoyo, located at Km 7½ of the Babahoyo - Montalvo road, with an altitude of 8 meters above sea level. Coordinates X: -1,799621, - Y: 79,473936. The study topic was: influence of plant hormones on the development and growth of the zucchini (Cucurbita pepo) crop. The research objectives were to determine the influence of plant hormones on plant growth, identify the type of hormone that produces the best performance for the zucchini producer, analyze the benefit / cost ratio in each of the treatments. Zucchini was planted in 12m2 plots. Eight treatments with three repetitions were performed. Treatments were distributed in a complete randomized block design. For the evaluation of means, the Tukey test at 5% significance was used. During the cultivation cycle, the following were evaluated: length of the plant, days to flowering, fresh and dry weight of the root, days to physiological maturation, number of flowers per plant, number of fallen flowers, number of fruits per plant, weight of fruits, yield kg / ha, economic analysis. The results showed that the highest yield was obtained from treatment one with the application of auxin in doses of 0.5 cc / liter of water.